Novel water-soluble aromatic bisdiglycolamide masking agents for the separation of trivalent americium over lanthanides by NTAamide(n-Oct) extractant. Issue 2 (April 2023) - He, Lanlan; Wang, Xueyu; Li, Qiuju; Xiao, Xiao; Li, Fengfeng; Luo, Fangxiang; Pan, Qingjiang; Ding, Songdong
Abstract: Two novel water-soluble aromatic bisdiglycolamides (BisDGAs) of SO3 -TEX( m )-BisDGA (sodium bis((2-(2-(diethylamino)− 2-oxoethoxy)acetamido)methyl)benzenesulfonate) and SO3 -TEX( p )-BisDGA (sodium 2, 5-bis((2-(2-(diethylamino)− 2-oxoethoxy)acetamido)methyl)benzenesulfonate) were synthesized and used as masking agents for the selective extraction and separation of Am 3+ over Eu 3+ in HNO3 solutions by N, N, N′, N′, N′′, N′′ -hexaoctylnitrilotriacetamide (NTAamide( n -Oct)) in n -dodecane. Their influences on the separation effect of Am 3+ over Eu 3+ were investigated and compared with that of a water-soluble aliphatic bisdiglycolamide of N, N, N′′′, N′′′ -tetraethyl- N′, N′′ -ethidene bisdiglycolamide (TEE-BisDGA) reported by our previous work. SO3 -TEX( m )-BisDGA and SO3 -TEX( p )-BisDGA exhibit significantly better masking effects than TEE-BisDGA. The masking selectivity for Eu 3+ over Am 3+ follows the order of SO3 -TEX( m )-BisDGA > SO3 -TEX( p )-BisDGA > TEE-BisDGA. During the extraction process, the three BisDGA masking agents form the 1:2 complexes, while the NTAamide ( n -Oct) extractant forms the 1:1 complexes with Am 3+ and Eu 3+ . Meanwhile, the conditional stability constants (log β ) for the three masking agents with Eu 3+ were calculated using the least squares method, which are also in line with those obtained from fluorescence spectrometry (FS). By means of FS, time-resolved laser-induced fluorescence spectrometry (TRLFS), Fourier Transform infrared spectrometry (FT-IR), conductivity, and electrospray ionization mass spectrometry (ESI-MS) analyses, the composition of the complex of Eu 3+ with water-soluble BisDGAs (L) was determined to be [Eu(NO3 )2 (H2 O)∙2L](NO3 ). Furthermore, a batch simulation of multistage countercurrent extraction with 12-stage extraction, 4-stage scrubbing and 8-stage stripping was carried out and demonstrates a highly efficient separation of Am 3+ over Lns 3+ with the recovery rates above 99.9 % for all metal ions in the simulated feed solution, and with the decontamination factors more than 500 between Am 3+ and most of the lanthanide ions. Graphical Abstract: ga1 Highlights: The aromatic SO3 -TEX( m )-BisDGA has a significantly better masking effect than the aliphatic TEE-BisDGA. The selectivity for Eu 3+ over Am 3+ follows the order of SO3 -TEX( m )-BisDGA > SO3 -TEX( p )-BisDGA > TEE-BisDGA. The composition of complexes was determined by the analyses of FS, TRLFS, FT-IR, ESI-MS and conductivity. A batch simulation of multistage countercurrent extraction demonstrates a highly efficient separation of Am 3+ over Ln 3+ .